The Effect of Wind Velocity and Night Natural Ventilation on The Inside Air Temperature in Passive Cooling in Arid Zones the Effect of Wind Velocity and Night Natural Ventilation on The Inside Air Temperature in Passive Cooling in Arid Zones - Ben Cheikh, Nhamida (ICONARCH International Congress of Architecture and Planning, 2014)
The effect of wind velocity and night natural ventilation in lowering the inside daytime air temperature in passive cooling in arid zones, were investigated by numerical calculations and experimental means for different values of air change flow rate due to infiltrations and natural ventilation and different wind speed. The numerical calculations based on the inside outside air temperature, wind speed, cracks and openings dimensions to determine the volume of air change per hour. The experimental model was a test cell with door facing north and window in the opposite side facing south, the volume of the model was 9m³. The calculated and measured results show that 1.8 volume per hour of air change flow rate and 2m/s wind speed show a high concordance between calculated and measured inside air temperature, and can lower the inside air temperature by 3°c to 4°C compared to non ventilated test cell (Bencheikh & Bouchair 2004) .